1999
DOI: 10.1007/bf02253669
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms for the antiarrhythmic action of cinnamophilin in rat heart

Abstract: We investigated the electrophysiological effect and antiarrhythmic potential of cinnamophilin (Cinn), a thromboxane A(2) antagonist isolated from Cinnamomum philippinense, on rat cardiac tissues. Action potential and ionic currents in single rat ventricular cells were examined by current clamp or voltage clamp in a whole-cell configuration. In 9 episodes of ischemia-reperfusion arrhythmia, 10 microM Cinn converted 6 of them to normal sinus rhythm. Cinn suppressed the maximal rate of rise of the action potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
2
17
2
Order By: Relevance
“…Moreover, cinnamophilin was reported to protect ischaemic skeletal muscle from the reperfusion injury in rats ( Cheng and Chang, 1995 ) and to act as a novel antioxidant and cytoprotectant against oxidative damage ( Hsiao et al , 2001 ). In a recent study performed in isolated Langendorff‐perfused rat heart, cinnamophilin was effective in the reduction of the coronary artery ligation/reperfusion‐induced arrhythmias ( Su et al , 1999 ). This profile of activity may be attributed to its electrophysiological actions such as blockade of the transient outward K + ( I to ), Na + and Ca 2+ channels ( Su et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, cinnamophilin was reported to protect ischaemic skeletal muscle from the reperfusion injury in rats ( Cheng and Chang, 1995 ) and to act as a novel antioxidant and cytoprotectant against oxidative damage ( Hsiao et al , 2001 ). In a recent study performed in isolated Langendorff‐perfused rat heart, cinnamophilin was effective in the reduction of the coronary artery ligation/reperfusion‐induced arrhythmias ( Su et al , 1999 ). This profile of activity may be attributed to its electrophysiological actions such as blockade of the transient outward K + ( I to ), Na + and Ca 2+ channels ( Su et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study performed in isolated Langendorff‐perfused rat heart, cinnamophilin was effective in the reduction of the coronary artery ligation/reperfusion‐induced arrhythmias ( Su et al , 1999 ). This profile of activity may be attributed to its electrophysiological actions such as blockade of the transient outward K + ( I to ), Na + and Ca 2+ channels ( Su et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reentry and oscillatory after potential are two mechanisms proposed to be responsible tor the induced arrhythmia [14]. Based on studies on rat cardiac tissues, Suet al [16] reported that cinnamophilin, a thromboxane A 2 antagonist isolated from Cinnamomum philippinense, exerts antiarrhythmic activity by prolonging the duration and inhibiting the upstroke of action potential. They further showed that inhibition of sodium, caldum and transient outward potassium currents may underlie the observed antiarrhythmic actions.…”
mentioning
confidence: 99%
“…Reentry and oscillatory after potential are two mechanisms proposed to be responsible for the induced arrhythmia [14]. Based on studies on rat cardiac tissues, Su et al [16] reported that cinnamophilin, a thromboxane A 2 antagonist isolated from Cinnamomum philippinense, exerts antiarrhythmic activity by prolonging the duration and inhibiting the upstroke of action potential. They further showed that inhibition of sodium, calcium and transient outward potassium currents may underlie the observed antiarrhythmic actions.…”
mentioning
confidence: 99%